Quichotte : a novel - Rushdie, Salman; Gene Berry and Jeffrey Campbell Collection (Library of Congress) (London : Jonathan Cape ; Random House, 2019)
"Quichotte, an aging traveling salesman obsessed with the "unreal real" of TV, falls in impossible love with a queen of the screen; while obsessively writing her love letters, he wishes an imaginary son, Sancho, into existence. Together they set off across America in Quichotte's trusty Chevy Cruze to find her and convince her of his love. Meanwhile, Quichotte's tragicomic story is being told by the author who created him: Brother, a mediocre spy novelist in the midst of a midlife crisis. As their stories intertwine, we are taken on a wild, picaresque journey through a country on the edge of moral and spiritual collapse. Just as Cervantes wrote Don Quixote to satirize the culture of his time, Rushdie brings us a new twist on a classic. Quichotte is a profoundly human love story and a wickedly entertaining satire of a corrupt age in which fact is so often indiscernible from fiction. With unforgettable characters and riveting suspense, this dazzling novel showcases an essential storyteller at his brilliant best"--
Keywords: Novelists -- Fiction; Midlife crisis -- Fiction; Voyages and travels -- Fiction; FICTION / Literary; FICTION / Sagas; Psychological fiction